Olanzapine for young PEople with aNorexia nervosa (OPEN): results of a feasibility study - Olena Said; Dominic Stringer; Ece Sengun Filiz; Hiba Mutwalli; Sevgi Bektas; Melahat Nur Akkese; Vanessa Kellermann; Katie Ireland; Elizabeth Tyrrell-Bunge; Demelza Beishon-Murley; Joel W. T. Khor; Lee Allman; et al. (BMC Psychiatry)
Abstract Background Despite the availability of evidence-based treatments for anorexia nervosa (AN), remission rates are moderate, and mortality is high. Olanzapine is used as adjunct therapy for AN in case of insufficient response to first-line treatments, even though the evidence is limited. Its effect on eating disorder (ED) psychopathology, its efficacy and tolerability, and its acceptability and adherence rate are unclear. Methods We assessed the feasibility of a future definitive trial on olanzapine in young people with AN in an open-label, one-armed feasibility study that aimed to include 55 patients with AN or atypical AN aged 12–24 who gained < 2 kg within at least one month of treatment as usual (TAU) during outpatient, inpatient, or day-care treatment. Time points for assessments were at baseline, 8 weeks, 16 weeks, and 6 or 12 months. We estimated the following planning parameters: Recruitment rate (number of patients who agreed to take olanzapine/number eligible), adherence rate (number adhering to treatment/number recruited) and attrition rate (number completing study assessments/number recruited). In addition, two exploratory effect size parameters were estimated: Mean change in body mass index (BMI) and mean change in ED psychopathology. Results Fifty-two people were pre-screened (June 2022 to May 2023; 10 study sites in England). 13 were ineligible at pre-screening . Of the 39  approached, 4 were found ineligible at screening. Of the remaining 35 eligible, 10 declined and 5 did not take part for other reasons. Thus, 20 participants were recruited and started olanzapine (recruitment rate: 20/35 = 57%). 15 out of 20 (75%) continued olanzapine for ≥ 16 weeks, and 13 participants (65%) remained in the trial until follow-up (either 6 or 12 months). Participants experienced, on average, a decrease over time in their Eating Disorder Examination Questionnaire (EDE-Q) Global scores (0.07 per week, N = 20) and an increase in BMI (0.08 kg/m2 per week, N = 20) during treatment with olanzapine plus TAU. Conclusions Possible reasons for the recruitment difficulties and low adherence rate include the high clinical workload of ED services during the COVID-19 pandemic and the reluctance of patients to agree to take olanzapine under the relatively restricted conditions of a clinical study. Trial registration International standard randomised controlled trial register number: ISRCTN80075010. Registration date: 27/04/2022.